Influence of repeated ochratoxin A ingestion on milk production and its carry‐over into the milk, blood and tissues of lactating cows. (10th September 2015) - Hashimoto, Yasushi; Katsunuma, Yu; Nunokawa, Masahiro; Minato, Hajime; Yonemochi, Chisato
Abstract: An experiment was conducted to investigate the influence of repeated ingestion of ochratoxin A (OTA) on milk production of lactating Holstein cows over 28 days, and the carry‐over of OTA from the diets into the milk and tissues of the cows. Nine cows were divided into three groups, labeled OTA5, OTA50 and OTA100, and fed a diet containing 5, 50 and 100 µg OTA/kg of dry matter, respectively. Body weight, feed intake and daily milk yield in cows were not different among the three groups during the OTA‐intake period. OTA residues were neither detected in the tissues, such as liver, kidney, muscles, fat and jejunoileum, nor in the milk of any cows in the OTA intake groups. In contrast, a small amount of OTA (0.1 µg/kg) was detected in the blood plasma of one sample in the OTA50 group and multiple samples in the OTA100 group. The results of this study show that the ingestion of diets containing up to 100 µg/kg of OTA over 28 days does not affect feed intake or milk production of cows, and the dietary OTA is not carried over into milk and edible tissues such as the liver, muscles and fat. © 2015 Japanese Society of Animal Science